Growth performance and mineral analysis of Pleurotus ostreatus from various agricultural wastes mixed with rubber tree sawdust in Malaysia - Fathie, Ahmad Zakil; Lim, Hui Xuan; Norafira, Zaman; Nurul Idayu, Alan; Nurul Adila Aida, Salahutheen; Mohd Shafiq, Mohd Sueb; Ruzinah, Isha (Elsevier, 2021)
This study aims to contrast the impacts of various agricultural wastes on the development, yield and mineral content of P. ostreatus. All substrates were added 5% by weight dry wheat bran and 1.5% by weight dry calcium carbonate and sterilized at 100 ◦C for 8 h using a sterilization chamber. The best substrate to obtain a greater total weight of fresh mushrooms and biological efficiency was 50% SB + 50% SR (207.87 g/bag; 78.44%) with mycelial growth at 26 ± 2 days. All of the agricultural wastes used in this study have abundant potassium (K) content as it is the mineral element needed for the mushroom growth. Therefore, the potassium (K) was the maximum macroelement in concentration as compared to other nutrients and all heavy metal content were not detected in the first fresh mushroom harvested. Therefore, SB seemed to be a better alternative material to grow P. ostreatus.